Antecedents of Improving Service Performance Innovation in Food and Beverage Start Up Businesses - Wahyuningsih, Sri Handari; Astuty, Isthofaina; Makarim, Habib Zhafran; Rizqi, Maulidyah Amalina (Universitas Muhammadiyah Ponorogo, 2025)
Service innovation is currently a challenge for every business, including start-up food and beverage businesses in Yogyakarta. This study aims to test the importance of service performance innovation by considering positive Thriving at work behavior as a mediator, with antecedents of Leader Member Exchange (LMX) and co-worker support. The approach used in the study is a quantitative approach. The study was conducted by taking a Food and beverage startup business, a Cafe service in the Yogyakarta area. Using Path Analysis and Sobel test, the results show the influence of LMX on Thriving at work, the influence of co-worker support on thriving at work, and the influence of co-worker support on service performance innovation. The results of this study provide implications for the importance of building a model for improving business service performance innovation through positive thriving at work behavior and organizational processes, namely leader member exchange and co-worker support, especially in the context of the food and beverage business.